Corporate tax credit and trade credit financing: based on the analysis of non-public companies - Le Zhao; Qingyang Tang; Muzhi Wang (China Journal of Accounting Studies)
Based on the tax credit rating disclosure system, we examine the impact of the tax credit rating on trade credit levels within non-public companies and analyse the specific mechanisms through which the tax credit rating affects trade credit financing. Our results indicate that companies with the tax credit rating of A (indicative of a higher tax credit) tend to receive increased trade credit. Further analysis reveals that the positive relationship between tax credit and trade credit financing is more pronounced when the customer firm lacks transaction history with its suppliers, operates in the region with a lower trust level or a lower degree of marketisation, or holds weaker bargaining power compared to its suppliers. This study enriches the relevant literature on the economic consequences of tax credit rating, highlighting its effectiveness in alleviating information asymmetry and financial constraints among non-public firms, and also extends the field of how impartial and authoritative regulators affect trade credit financing.